On the interaction of growth, trade and international macroeconomics - Clemens C. Struck (University College Dublin, UCD School of Economics, 2017)
Standard economic theories have severe difficulties in simultaneously explaining a number of key aggregate empirical facts: i) there are substantial differences in capital-labor ratios across time ii) despite continuously increasing capital-labor ratios, both factors still earn non-negligible shares in income iii) labor hours per capita are rather stable amid expanding consumption possibilities iv) price levels are higher in more developed countries v) there are no large gains from factor-proportions trade vi) the world trade-to-output ratio increases over time. I argue that standard economic theories ignore the vast improvements in goods quality and new products. I present an augmented standard model that incorporates these features and jointly rationalizes these six empirical facts.
Keywords: E23; E24; F11; F31; O41; 330; Engel's law; product quality and varieties; structural change; growth; trade; price levels